Investigation and Comparison of Communication Network and Expression of KLF4 and POU5F1 Genes During Spermatogenesis - Maedeh Yazdani Dizicheh; Hossein Azizi; Dariush Gholami; Amir Khaki (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Spermatogenesis is the primary process of sperm production occuring in seminiferous tubules. Spermatogonial stem cells (SSCs) have the ability for self-renewal, differentiation, and the transmission of genetic information to subsequent generations. KLF4 and POU5F1 are transcription factors expressed in a wide range of tissues and play key roles in such processes as apoptosis, differentiation, proliferation, and cellular development. The present study aimed to assess the expression levels of KLF4 and POU5F1 genes in mouse embryonic stem cells (mESCs), spermatogonial stem cells (SSCs), embryonic-like stem cells (ES-like), and testicular cells, and identify the signaling pathways associated with them in the process of spermatogenesis. Materials & Methods: In this experimental study, spermatogonial cells were extracted from mouse testes using enzymatic digestion method and cultured in GSC medium containing FGF, EGF, and GDNF. Thereafter, the expression of KLF4 and POU5F1 genes was examined in mESCs, SSCs, ES-like, and testicular cells was investigated using immunocytochemistry, immunohistochemistry, and reverse transcription-polymerase chain reaction methods, and protein-protein interactions and signaling pathways were evaluated using bioinformatics methods. Results: The KLF4 and POU5F1 genes exhibited positive expression in ES-like cells and testicular cells. The assessment of KLF4 mRNA and POU5F1 mRNA expression levels demonstrated that KLF4 expression is higher in mESCs and ES-like cells compared to other cells, while POU5F1 expression is higher in SSCs. Both KLF4 and POU5F1 are considered essential and powerful genes that share a common class and function. Conclusion: The findings of this study indicated that KLF4 and POU5F1 play crucial roles in the proper development of sperm and are present in various types of cells, including mESCs, SSCs, ES-like cells, and testicular cells. These factors are key components of sexual stem cells and contribute to stem cell proliferation, making them potential diagnostic markers for these cell lines.